There Is No Kurdish Art. (1st January 2018) - Cockrell-Abdullah, Autumn
Abstract : This essay considers the powerful practice of art in Iraqi Kurdistan as it balances practices and nationalities, values and identities to create an aesthetic that is uniquely Kurdish in its expression. This examination of contemporary Kurdish art begins by considering the challenges to writing about the visual arts in Kurdistan and discusses some of the indigenous projects that have worked to create an arts infrastructure to preserve and promote the arts in the city of Sulaimani. While reflecting on Kurdish legacies within Iraq, this essay further interrogates the contemporary products of a combined heritage and questions what pieces of this historical legacy will be brought forward into the future of Kurdistan.